ANALISIS PERSEPSI PELANGGAN TERHADAP MEBEL EDISTA TIMIKA - Rosalia Ida Refra; Habel Taime (CV. ADIBA AISHA AMIRA, 2023)
This study aims to measure the influence of customer perceptions of Timika Edista Furniture by using a quantitative approach. The data collection technique used was a questionnaire. The data analysis technique used is the z test with a significance level of 5%. The results of this study indicate that: the average customer perception of Furniture Edista Timika is above 80% of the ideal value